Regional studies on economic growth, financial economics and management : proceedings of the 19th Eurasia Business and Economics Society Conference - Bilgin, Mehmet Huseyin; Danis, Hakan; Demir, Ender; Can, Ugur (Eurasian studies in business and economics, 2017)
This volume presents selected papers from the 19th Eurasia Business and Economics Society (EBES) Conference held in Istanbul. Its primary emphasis is on showcasing the latest empirical research on social change, sustainable development and the management of public and private organizations in emerging economies. The respective articles also address more specialized and related topics such as financial risk tolerance, international strategic partnerships, female labor force participation, human capital dynamics, and economic integration, among others.